4+4q=6+3q

Simple and best practice solution for 4+4q=6+3q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+4q=6+3q equation:


Simplifying
4 + 4q = 6 + 3q

Solving
4 + 4q = 6 + 3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-3q' to each side of the equation.
4 + 4q + -3q = 6 + 3q + -3q

Combine like terms: 4q + -3q = 1q
4 + 1q = 6 + 3q + -3q

Combine like terms: 3q + -3q = 0
4 + 1q = 6 + 0
4 + 1q = 6

Add '-4' to each side of the equation.
4 + -4 + 1q = 6 + -4

Combine like terms: 4 + -4 = 0
0 + 1q = 6 + -4
1q = 6 + -4

Combine like terms: 6 + -4 = 2
1q = 2

Divide each side by '1'.
q = 2

Simplifying
q = 2

See similar equations:

| 6x+10=109-5x | | 11x^2=18 | | 4y=2(10-y) | | 6x+21=57 | | 8y-6=2y+5 | | 8+n=2 | | 8r^2+2=7r^2 | | 3y=2(10-y) | | 6+9x=38+x | | 6x+3=5x | | 10-2(x-7)=-4 | | 50=2x+12x | | 6-2z=-12 | | 2x+5=29 | | 2x-4=12x-34 | | y+4=x | | 3x^4-6x^2=0 | | 161-2x=25x+20 | | 1.75m+3=12 | | 5x+20=12x-57 | | 6-8x=51-43x | | 3x+9=5x-13 | | -7+(-7)= | | 6.3-.3x=-4.2 | | 3a=-8+a | | 7x-1.8=-4x+0.4 | | X^2-ax-bx-ab=0 | | 9x-41=3x+1 | | -6x-3.9=-7x-4.1 | | 2.3X+10=16 | | 114-4x=3x+9 | | 2-4b=2+3 |

Equations solver categories